Chemical functionalization of palm fibers for improved dye adsorption: sustainability and efficiency (International Journal of Biology and Chemistry, 2026)
The potential of chemically modified palm fibres (CMPF) as effective, economical, and eco-friendly sorbents for wastewater treatment – more specifically, for dye removal – is highlighted in this study. Two adsorbents were produced from palm fibres: acid-base treated palm fibres (A-BTPF), treated with H₂SO₄ and NaOH, and CMPF, treated with CS₂. The addition of xanthate and aldehyde functional groups to CMPF, which enhanced its adsorption ability, was validated by FT-IR analysis. Adsorption behavior was assessed for neutral red (NR) and methyl green (MG) dyes under varying pH, contact time, adsorbent dose, initial dye concentration, and temperature. Both adsorbents demonstrated significant removal efficiencies, with maximum adsorption of NR at pH 4 and MG at pH 10. The enhanced adsorption of MG at basic pH is consistent with the adsorbent's pHPZC value of 9.0. Adsorption data were best described by the Langmuir isotherm model, with maximum adsorption capacities of 19.88 mg/g for NR and 7.45 mg/g for MG, and correlation values of 0.9935 and 0.9869, respectively. Kinetic investigations showed that adsorption followed a pseudo-second-order model (R² = 0.9988 for NR and 0.9989 for MG). Thermodynamic analysis confirmed that the process was spontaneous and endothermic (negative ΔG° and positive ΔH° values). CMPF exhibited superior adsorption efficiency and capacity compared to A-BTPF, demonstrating its suitability as a high-performance, sustainable biosorbent for wastewater treatment. Given its low cost, abundance, and enhanced adsorption performance, CMPF has strong potential for industrial-scale applications, particularly in textile, pharmaceutical, and dye-producing industries, offering a green alternative to conventional adsorbents in water purification.Keywords: Biosorption, Xanthated palm fiber, Dye removal, Wastewater treatment, Adsorption isotherms, Adsorption kinetics